Plants and the ecosystem - Billings, W. D. (MacMillan and Co., Ltd., 1964)
This book is an elementary introduction to ecology. Emphasis is given to the relationships of plant individuals and populations to their environments and to their roles in ecosystems. The text is directed to the reader who knows little or nothing about ecology.